Meeting the Universe Halfway : Quantum Physics and the Entanglement of Matter and Meaning - Barad, Karen Michelle (Book collections on Project MUSE., 2007)
A theoretical physicist and feminist theorist, Karen Barad elaborates her theory of agential realism, a schema that is at once a new epistemology, ontology, and ethics.